2010
DOI: 10.1128/jvi.02642-09
|View full text |Cite
|
Sign up to set email alerts
|

PB2 Residue 271 Plays a Key Role in Enhanced Polymerase Activity of Influenza A Viruses in Mammalian Host Cells

Abstract: The direct infection of humans with highly pathogenic avian H5N1 influenza viruses has suggested viral mutation as one mechanism for the emergence of novel human influenza A viruses. Although the polymerase complex is known to be a key component in host adaptation, mutations that enhance the polymerase activity of avian viruses in mammalian hosts are not fully characterized. The genomic comparison of influenza A virus isolates has identified highly conserved residues in influenza proteins that are specific to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
198
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(218 citation statements)
references
References 45 publications
7
198
3
Order By: Relevance
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…For this test we employed the H3N2 Nanchang strain, which is a well characterized avian strain cloned directly from birds and has never been exposed to humans (21). This avian influenza strain replicates efficiently at high temperatures in avian cells and contains E at the 627 position in PB2 (27). In addition, we introduced the human E627K mutation to the PB2 subunit of the avian Nanchang Pol complex.…”
Section: Effect Of the Human E627k Pb2 Mutation On Temperaturedependementioning
confidence: 99%
“…Moreover, the 2009 H1N1 pandemic virus also harbours PB2-E627, but additionally possesses a lysine at position 591 (PB2-E591K), which is able to partially, but not completely, compensate for the lack of the PB2-E627K mutation 10,11 , suggesting that other adaptive factors may account for the efficient replication of these viruses in humans. Other mutations in PB2, known to have a role in host adaptation, are the exchange of aspartic acid with asparagine at position 701 (PB2-D701N), which can confer high pathogenicity to avian H5N1 and H7N7 viruses in mice 4,12 and the substitution of threonine with alanine at position 271 (PB2-T271A), which has been suggested to enhance polymerase activity in mammalian cells 13 . Furthermore, adaptation to human importin α might have a crucial role in interspecies transmission and pathogenicity 15,16 .…”
mentioning
confidence: 99%